Lactate dynamics of mountain bikers in a laboratory performance diagnostic - Ahrend, M.; Schneeweiss, P.; Theobald, U.; Niess, A. M.; Krauss, I. (Journal of Science and Cycling, 2015)
Background: Caused by a multitude of climbs and downhill sections, as well as overtaking manoeuvres, intense intermitted physiological demands are characteristic for mountain bike marathon and cross country competitions. Consequently, aerobic and anaerobic parameters are of importance for the individual`s race performance (Impellizzeri and Marcora, 2007: Sports medicine 37(1), 59---71). Considering that only 40% of the variance in performance are explained by aerobic fitness in high---level mountain bikers, anaerobic parameters are rarely analysed (Impellizzeri and Marcora, 2007) and athletes have high blood lactate concentrations during a mountain bike race (Prins et al., 2007: J Sports Sci., 25(8), 927---35), tolerance of high lactate accumulation and faster lactate elimination could be an important factor of performance.